PENGGUNAAN MEDIA PAPAN PECAHAN PADA MATERI PECAHAN SEKOLAH DASAR DI ERA MERDEKA BELAJAR - Yani, Rasyida; Hamimi, Lia (Universitas Islam Sumatera Utara, 2024)
The purpose of this research is to improve learning outcomes in learning fraction materials using innovative media in the form of fraction board props as teaching aids. This quantitative research uses an experimental design. The experimental design used was Pre-experimental Design on One Group Pretest-Postest type. The sample consisted of 11 students of class V SDN 15 Blangpidie. Data collection was carried out using a test instrument. The data analysis technique was carried out using the Wilcoxon Test because the sample used was a saturated sample of less than 30. The results obtained in this study were an increase in student learning outcomes on fraction material with the acquisition of the average pretest and post-test scores of students were 23.45 and 64.09. Based on the results of the Wilcoxon Test calculation, it is concluded that there is a substantial influence in increasing the learning outcomes of grade V students of SDN 15 Blangpidie.